TOLERANSI UDANG REGANG Macrobrachium sintangense TERHADAP SALINITAS - Bambang Irawan; Indinah; Hani Sudarmanto (The East Java Biological Society, 1996)
Experiment on salinity tolerance in Macrobrachium sintangense was conducted. The result showed that Macrobrachium sintangense has a wide salinity tolerance and all individuals could survive in the experimental medium up to 20 ppt salinity level, but no individuals could survive in the 35 ppt salinity more than 24 hours.